Mariological Interpretation of the Eight Beatitudes (Matt 5:3–10) - Wołowski, Lech (Collectanea Theologica, 2021)
The article examines the question of the Mariological interpretation of the eight beatitudes contained in Matt 5:3–10. Christian theologians of all ages, from Clement of Alexandria to the authors of contemporary biblical commentaries, have proposed various interpretations of this biblical text. Among the multitude of interpretations developed throughout history, the Mariological aspect appears quite rarely. Yet, as Pope Benedict XVI observes, the very biblical Marian title “Blessed” should direct the theological thought to the Mariological aspects of this issue. In modern times, a very deep reflection on the subject was conducted by two great theologians of the XX century, J. Ratzinger (Benedict XVI) and H.U. von Balthasar. On the Polish ground, the task was partly undertaken by J. Tischner, who elaborated the theme of eight beatitudes in the key of the Marian pilgrimage of the nation. The present work is meant to deepen the Mariological-biblical analysis of the eight beatitudes and revive the discussion regarding this subject in the perspective proposed by Benedict XVI, to understand the beatitudes as a program of life for a modern Christian.